(NdEWQNOSTO TRETIJ GOD(B:s (NrOMAN (B/s - (Ng@GO w(B.s ((NwIKTOR(B)s ((NmINSK(B:s (NmASTACKAQ L(Bi(NTARATURA(B,s, 1985)
(NrOMAN WYDA@]EGSQ PISATELQ fRANCII wIKTORA g@GO (B"(NdEWQNOSTO TRETIJ GOD(B" (NPOSWQ]EN FRANCUZSKOJ BURVUAZNOJ REWOL@CII KONCA (BXVIII (NWEKA(B. (NaWTOR PROSLAWLQET REWOL@CI@(B, (NGEROIZM NARODA(B, (NSAMOOTWERVENNU@ BORXBU REWOL@CIONNYH SIL PROTIW SOCIALXNOGO GNETA I TIRANII(B.s
(NiNW(B.: 37914, 249566s
(NtIRAV(B: 300 000 (N\KZ(B.s